Lens fluorescence and metabolic control in type 1 diabetic patients: a 14 year follow up study. Issue 9 (17th August 2004) - Kessel, L; Sander, B; Dalgaard, P; Larsen, M
Abstract : Background/aims: In this prospective study the authors followed the post-translational modification of the proteins of the lens of the eye by fluorometry over a period of 14 years in patients with type 1 diabetes mellitus. Methods: Twenty patients were examined at 6 years (baseline) and 20 years (follow up) after onset of diabetes mellitus. Glycaemic levels were assessed from HbA1c measured at regular intervals from the onset of diabetes mellitus. Results: Lens fluorescence at follow up was significantly related to mean HbA1c during the study period and to lens fluorescence at baseline (p<0.0001). Sixty per cent of the variation in rate of increase in lens fluorescence during the study period was statistically attributable to glycaemia levels. Conclusion: The results confirm that the rate of fluorophore accumulation in the lens of adult diabetic patients is increased in proportion to glycaemic control. This parameter alone is, however, not sufficient to explain the entire variation in lens fluorophore accumulation. Consequently, lens fluorescence must be influenced by other factors before initiation and during the study period, and possibly even before onset of diabetes mellitus. The underlying mechanism could be a variation in susceptibility to lens protein denaturation by glycation.